1995
DOI: 10.1002/elan.1140070403
|View full text |Cite
|
Sign up to set email alerts
|

Electrode modification with a poly(NiII‐tetramethyldibenzotetraaza[14]annulene) film. Electrochemical behavior and redox catalysis in alkaline solutions. I

Abstract: The voltammetric behavior in alkaline solution of a nickel-based chemically modified electrode (Ni-CME) prepared by oxidative electropolymerization of a nickel-tetraazaannulene complex (Ni"L) was investigated. After electrochemical deposition of the (Ni"L), film in dichloromethane on a conducting substrate, the modified electrode was continuously cycled in alkaline solution until a steady voltammetric profile was obtained. Although upon electrochemical treatment in basic solutions the nickel-nitrogen tetracoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 41 publications
(21 reference statements)
4
38
0
1
Order By: Relevance
“…As the cycling continues, the peaks grow steadily until they reach a steady state where no further growth is observed. This is typical of cyclic voltammograms recorded for electroformed nickel macrocyclic-based films in alkaline solution and shows that the film has been formed as a result of the anodic polymerization of the macrocyclic complex [32]. The CV shows one redox couple with formal potential (E 1/2 ) at ca.0.42 V vs. Ag j AgCl, which is assigned to the N(II)/Ni(III) redox process of the nickel centre of the NiTAPc.…”
Section: Cyclic Voltammetric Characterisationmentioning
confidence: 95%
“…As the cycling continues, the peaks grow steadily until they reach a steady state where no further growth is observed. This is typical of cyclic voltammograms recorded for electroformed nickel macrocyclic-based films in alkaline solution and shows that the film has been formed as a result of the anodic polymerization of the macrocyclic complex [32]. The CV shows one redox couple with formal potential (E 1/2 ) at ca.0.42 V vs. Ag j AgCl, which is assigned to the N(II)/Ni(III) redox process of the nickel centre of the NiTAPc.…”
Section: Cyclic Voltammetric Characterisationmentioning
confidence: 95%
“…Moreover, the procedure for their preparation is usually simple and the properties of the resulting coating can be controlled carefully. Electropolymerization procedure was used successfully for modifying electrode surfaces with Ni(II) cyclam and other similar Ni(II) tetraazamacrocyclic complexes [4] or Ni(II) tetramethyldibezotetraaza (14)anulene [5], and the resulting films showed high catalytic activity toward electrooxidation of alcohols and/or other À OH and À NH 2 containing compounds, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the formation of Ni(II) 3 Ni(III) are reported in several systems viz. Ni(II)-peptide [26] and Ni(II)-porphyrin [27]. The studies thus provide information regarding electroactivity, redox system and stability of the complex.…”
Section: Resultsmentioning
confidence: 98%
“…The Ni(II) 3 Ni(III) conversion at low potential may probably serve as a fast electrontransfer mediator for the oxidation of phenol as evident by the enhanced oxidation of phenol at the complex modified graphite electrode. It has been already reported that electrochemically formed nickel porphyrin coated electrodes exhibit good electrocatalytic activity for the oxidation of carbohydrates, benzyl alcohol [27], methanol, ethanol, propanol and hydrazine etc. [28,29].…”
Section: Resultsmentioning
confidence: 99%